Ranked junior tennis player injury survey - Hamilton, S. (1999)
The purpose of the survey was to determine the extent of injuries among junior tournament players, the kinds of injuries and their playing, practice and exercise routines. The survey was sent to 900 of the country`s ranked tennis juniors. There were 492 respondents (272 boys, 220 girls) from 39 states, with and average age of 14.8 years. Their average numbers of years playing were 7.6 for males and 7.0 for females. Both groups practised an average of 2.3 hours per day. Their average number of tournaments played per year was 17. Of the 492 players, 453 were in a regular exercise routine and 298 used weights. 306 players (62%) had had one or more injuries that required a visit to a doctor and kept them out of tennis for at least three days, resulting in an average of 1.8 injuries per player per year. The most common injury locations were the ankle (32%), shoulder (31%), knee (30%), back (26%) and wrist (20%). The alarming amount of injuries among juniors indicates there might be a need for a season for juniors. Further research is needed to identify the types of injuries, training methods, the extent of practice and tournament play, in order to develop individualised injury-avoidance techniques.